B-Cell-Specific Myd88 L252P Expression Causes a Premalignant Gammopathy Resembling IgM MGUS - Schmidt, Kristin; Sack, Ulrike; Graf, Robin; Winkler, Wiebke; Popp, Oliver; Mertins, Philipp; Sommermann, Thomas; Kocks, Christine; Rajewsky, Klaus (Frontiers in Immunology, 2020)
A highly recurrent, somatic L265P mutation in the TIR domain of the signaling adapter MYD88 constitutively activates NF-kappaB. It occurs in nearly all human patients with Waldenström’s macroglobulinemia (WM), a B cell malignancy caused by IgM-expressing cells. Here we introduced an inducible leucine to proline point mutation into the mouse Myd88 locus, at the orthologous position L252P. When the mutation was introduced early during B cell development, B cells developed normally. However, IgM-expressing plasma cells accumulated with age in spleen and bone, leading to more than 20-fold elevated serum IgM titers. When introduced into germinal center B cells in the context of an immunization, the Myd88L252P mutation caused prolonged persistence of antigen-specific serum IgM and elevated numbers of antigen-specific IgM plasma cells. Myd88L252P-expressing B cells switched normally, but plasma cells expressing other immunoglobulin isotypes did not increase in numbers, implying that IgM expression may be required for the observed cellular expansion. In order to test whether the Myd88L252P mutation can cause clonal expansions, we introduced it into a small fraction of CD19-positive B cells. In this scenario, five out of five mice developed monoclonal IgM serum paraproteins accompanied by an expansion of clonally related plasma cells that expressed mostly hypermutated VDJ regions. Taken together, our data suggest that the Myd88L252P mutation is sufficient to promote aberrant survival and expansion of IgM-expressing plasma cells which in turn can cause IgM monoclonal gammopathy of undetermined significance (MGUS), the premalignant condition that precedes WM.